Maize Crop Agronomy for Enhancing Productivity in the Dryland of West Nusa Tenggara - Dewi, Pervitara Arum; Sudharmawan, A. A.; Sudantha, I Made (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Dryland agriculture continues to face numerous challenges that need resolution. Maize has emerged as an alternative food source, with additional uses as animal feed and biofuel. However, maize cultivation in the drylands of West Nusa Tenggara has yet to fully apply agronomic principles, resulting in suboptimal yields. This literature review evaluates key agronomic factors affecting maize productivity in West Nusa Tenggara’s drylands. The most suitable and marginally suitable land for maize among the three regencies was found in East Lombok, with soil pH (H2O) ranging from 5.8 to 7.4 (slightly acidic to neutral), total nitrogen (N) between 0.09–0.19% (low to moderate), available phosphorus (P) between 14.4–54.76 ppm (high to very high), and organic carbon (C) ranging from 0.4–0.8% (low). Soil texture includes sand (62.67–76.00%), silt (20.13–30.79%), and clay (2.59–11.71%), indicating a sandy loam to loamy sand composition. Seed varieties used in East Lombok include Bima 20 URI, Nasa-29, JH-37, Bima-14 Batara, JH 27, and HJ 21; West Sumbawa uses Bisi 18 and Jakarin; while North Lombok uses Gumarang, Lamuru, and NK 212. Traditional water conservation techniques are practiced in East Lombok and West Sumbawa, while sprinkler irrigation is employed in North Lombok. Fertilizers, including Trichocompost, Phonska, Urea, and rice husk biochar, are applied across East Lombok, North Lombok, and West Sumbawa. Integrated pest management (IPM) is applied in East Lombok and North Lombok to control fall armyworm (Spodoptera frugiperda) using refugia plants, and in West Sumbawa, microcontroller technology is used to manage monkey pests.